9.6%-Efficient all-inorganic Sb2(S, Se)3 solar cells with a MnS hole-transporting layer. Issue 6 (24th January 2022) - Qian, Chen; Li, Jianjun; Sun, Kaiwen; Jiang, Chenhui; Huang, Jialiang; Tang, Rongfeng; Green, Martin; Hoex, Bram; Chen, Tao; Hao, Xiaojing
Abstract : Post-annealing treatment to MnS can improve the interface quality, increase the carrier concentration in MnS and optimize the band alignment, leading to a high power conversion efficiency of 9.67% and excellent stability of Sb2 (S, Se)3 solar cells. Abstract : Antimony selenosulfide, Sb2 (S, Se)3, has emerged as a promising light-harvesting material due to its high absorption coefficient, suitable bandgap, and low-toxic and low-cost constituents. Previously, high-efficiency Sb2 (S, Se)3 solar cells were fabricated exclusively using Spiro-OMeTAD as the hole-transporting layer (HTL) with an n–i–p device architecture. However, the poor stability and high cost of the widely used Spiro-OMeTAD hole-transporting material may restrict its potential large-scale applications in solar cells. Here, we report stable and high-efficiency all-inorganic Sb2 (S, Se)3 solar cells enabled by an evaporated inorganic manganese sulfide (MnS) hole-transporting layer. MnS shows better valence band alignment with the Sb2 (S, Se)3 absorber than Spiro-OMeTAD. With post-deposition heat treatment, MnS demonstrates increased carrier concentration and work function. These in turn result in the highest efficiency of 9.67% in all-inorganic Sb2 (S, Se)3 solar cells. Moreover, the unencapsulated all-inorganic Sb2 (S, Se)3 solar cell demonstrates a remarkably enhanced stability compared to the Spiro-OMeTAD-based cells. These exciting results illustrate that MnS possesses a larger efficiency potential than Spiro-OMeTAD. This low-cost, efficient, stable, and up-scalable MnS hole-transporting layer may also be applicable to other emerging solar cells, paving a better pathway toward commercialization.